Clinical and Radiological Safety of Retained Implantable Doppler Devices Used for Free Flap Monitoring. Issue 1 (February 2022) - Kreutz-Rodrigues, Lucas; Gibreel, Waleed; Carlsen, Brian T.; Frick, Matthew A.; Mardini, Samir; Bakri, Karim
Introduction: Implantable Doppler devices are reliable adjuncts used for free flap monitoring. Occasionally, the probe/wire is not removed and remains in the soft tissues. The clinical safety of the retained probes and safety and compatibility with magnetic resonance imaging (MRI) have not been studied. We present a series of retained implantable Doppler probes examining clinic outcomes, safety and compatibility with MRI, and effect on MRI image quality. Methods: A retrospective review was conducted of patients who had an implantable Doppler device for free flap monitoring between July 2007 and August 2018. Routine post-operative imaging was reviewed for all patients to identify incidental findings of a retained probe. A subset of patients with retained implantable Doppler probes who underwent MRI was identified. Magnetic resonance images were reviewed to detect any degradation of image quality. Results: A total of 323 patients who had an implantable Doppler device placed were reviewed 18 (5.6%) patients were identified with a retained probe and were included in this study. Mean age was 49 years with mean follow-up of 34.4 months. One potential device-related complication occurred in 1 (5.6%) patient. A total of 32 MRI scans were performed in 8 patients with retained devices, including 6 patients who underwent a total of 21 MRIs of the surgical site. There were no complications related to the MRI scans, and we found no significant degradation of image quality. Conclusion: Retained implantable Doppler probes were not associated with substantial adverse clinical outcomes nor affected MRI image quality of the surgical site.